Pemetaan Partisipatif Desa Wisata Perintis Berbasis Social Enterprise Desa Cibubuan, Sumedang - Imran, Sarojini; Oktariflandi, Achfriyatama; Firmansyah, Riza; Noor, Laili Savitri; Hermawati, Ati (Jurnal Pemberdayaan Pariwisata; Vol 6 No 1 (2024): Jurnal Pemberdayaan Pariwisata, 2024)
Sumedang Regency is one of the areas in West Java Province, located precisely 45 km from Bandung City. It is crossed by the Bandung-Cirebon main route, and with its strategic location, it is a potential area for tourism, linking two cities that are already advanced in tourism. Sumedang Regency includes two sub-districts, namely North Sumedang and South Sumedang, with a total of 270 villages that have a variety of tourism potential that can be developed into tourist villages. However, to date, very few villages have been designated by the regional government as tourist villages. Even in the Anugerah competition Indonesian Tourism Village (ADWI) 2022, not a single village from Sumedang Regency was included. The urgency of legality is important in motivating the community to develop tourist villages and can protect village assets from intervention by outside control. Especially in North Sumedang, there is a lot of tourism potential that has not been managed collectively by village-owned enterprises (Bumdes), making it difficult to develop as a sustainable tourist destination. To overcome this problem, the Pancasila University Matching Fund team provided assistance with the pioneer village category for the Cibubuan Tourism Village. In this assistance activity, one of the programs implemented was participatory mapping, which was useful for collecting data on three important components of a tourist destination: attractions, accessibility, and amenities. Keywords: Cibubuan village, pioneer tourism village, social enterprise, participatory mapping